Metal-air battery charging monitoring system - KWON WANSUNG; JANG JAESUNG; SUNG JOON LEE; KIM, DONG JIN; SANGWON SEO; YOO JAE SANG (2024)
The subject to be solved in the present invention is to provide a charging monitoring system for metal-air batteries that can stably charge and manage the metal-air battery by checking whether the metal-air battery is damaged while charging an electrolyte and how much power is generated after the charging is completed in a state in which a plurality of metal-air batteries are fixated not to move. The charging monitoring system for the metal-air batteries comprises: an electrolyte charging device (1000) formed in a multi-layered structure, and charging an electrolyte and discharging by-products when a plurality of metal-air batteries (10) are fixated; an electrolyte concentration measuring member (2000) that checks the concentration of the charged electrolyte; a voltage measuring member (4000) that checks the voltage of the fixated metal-air batteries (10); a current measuring member (5000) that checks the current of the fixated metal-air batteries (10); an electrolyte leakage detection member (6000) that detects the leakage of the electrolyte from the fixated metal-air batteries; a temperature measuring member (7000) that measures the temperature of the electrolyte charging device (1000); and a monitoring center (8000) that warns a manager or the like when the measured electrolyte concentration, voltage, current, power, leakage information, and temperature exceed a reference range. 본 발명은 다수개의 금속공기전지를 움직이지 않도록 고정한 상태에서 안정적으로 전해질을 충전하면서 금속공기전지의 파손여부와 충전완료 후의 전력생산을 확인하여 안정적으로 금속공기전지를 충전하면서 관리할 수 있는 금속공기전지의 충전 모니터링 시스템에 관한 것이다. 본 발명의 주요구성은 다층 구조로 이루어지며 다수개의 금속공기전지(10)가 고정되면 전해질을 충전하고 부산물을 배출시키는 전해질 충전장치(1000)와, 충전되는 전해질 농도를 확인하는 전해질 농도측정부재(2000)와, 고정된 금속공기전지의 전압을 확인하는 전압측정부재(4000)와, 고정된 금속공기전지의 전류를 확인하는 전류측정부재(5000)와, 고정된 금속공기전지의 전해질 누출을 감지하는 전해질 누출감지부재(6000)와, 전해질 충전장치의 온도를 측정하는 온도측정부재(7000) 및 측정된 전해질농도, 전압, 전류, 전력, 누출정보, 온도가 기준범위를 벗어나면 관리자 등에게 경고하는 모니터링센터(8000)를 포함하는 것을 특징으로 한다.